Effect of Educational Program on Knowledge, Skills, and Personal Preparedness for Disasters Among Emergency Nurses: A Quasi-Experimental Study - Razan M. Al-qbelat MSN, RN; Maha. M. Subih PhD, RN; Malakeh Z. Malak PhD, RN (SAGE Publishing, 2022)
Continuous nursing education has a significant correlation with increasing knowledge, improving skills, and personal preparedness for disasters among nurses which leads to a decrease in mortality rate and enhances the quality of care. However, there is limited literature evaluating the effect of educational programs on the knowledge, skills, and personal preparedness for disaster preparedness among emergency nurses at Arab countries including, Jordan. This study evaluated the effect of an educational program on knowledge, skills, and personal preparedness for disasters among emergency nurses. A quasi-experimental study and one-group pretest-posttest design was used. A convenience sample was adopted to recruit registered nurses who are working in emergency rooms in the private and government health sectors in Jordan (N = 50). This study was conducted between May and June 2021. The intervention included an educational program consisting of 5 topics about disasters. The participants attended this program for 8 h over 1 week via Zoom application. There were significant differences between the pre-post educational intervention for knowledge ( t  = 4.79, P ≤ .001), skills ( t  = 6.66, P ≤ .001), and personal preparedness ( t  = 9.56, P ≤ .001) for disasters. These findings suggested the importance of implementing continuous education and training programs for emergency nurses about disasters due to increasing frequency of disasters worldwide.